Successes and Failures of Benjamin Disraeli’s Rhetoric and Heresthetics: Corn Laws, Franchise, and Empire - Iain McLean (Cahiers Victoriens et Edouardiens)
It is not news that Benjamin Disraeli was a reckless and shape-shifting politician. This chapter claims that he was one of those rare shape-shifters who practised what has been called ‘heresthetics’, namely the art and science of turning a losing position to a winning one. His manoeuvres in 1846 (Corn Laws), 1867‒68 (Reform) and 1876 (Royal Title Bill) show him at his heresthetic finest. Although it took him 30 years, he both destroyed and rebuilt the Conservative Party.